EMOTIONAL INTELLIGENCE IN BOARDING SCHOOLS: PERSPECTIVES OF MRSM TEACHERS - Syed Hassan, Syed Najmuddin; Rajikon, Muhd Akmal Noor; Yunus, Ahmad Rozelan; Aris, Amir; Mukapit, Mukhiffun; Mohd. Ishak, Noriah (Journal of Human Capital Development (JHCD), 2010)
As a new and young nation gained independence 50 years ago, there are many expectations about the new generation of citizen. One main foundation of building nationhood is in the area of education. Leaders, parents, employers and people on the street are talking about the state of education of the nation. Discussing about education, the focus would be the teachers – the engineers of tomorrow. What is their aspiration and conditions? Are they well equipped with the right tools, aptitude and attitude? Recent reports on teachers disruptive behaviors in the mass media called for urgent attention from the educational stakeholders. The increase in numbers of reported cases of misbehaving teachers would suggest many interlocking factors. One of the factors that may affect the teachers’ behavior is emotional stability. Emotional stability is crucial in facing challenges in the school environment. This study is trying to explore how the Malaysian teachers look at the emotional intelligence. This study aims to 1) identify components of emotional intelligence, 2) explore patterns that contribute to emotional intelligence, The study is conducted at 3 elite boarding schools which cater to cream of the crops students. Three teachers have consented to be participants in this case study design. The teachers consist are female teachers and their age from 30s and above. They are well experience teachers of more than ten years in service. Interview protocol was developed based on Goleman’s (1995) emotional intelligence construct. Three in-depth interviews are done. Using the protocol, teachers are asked about the concept of emotional intelligence. Data gathered was analyzed using NUD*IST software. The findings are a combination of what Goleman (1995, 1999) posited and a few new sub-factors emerged. These findings might be the emotional intelligence framework of Malaysian teachers. Keywords: education, emotional stability, emotional intelligence